System-level test and validation of hardware/software systems. - Sonza Reorda, M., ....-; Peng, Z., ....-; Violante, M., ....- (London : Springer, 2005)
"System-level Test and Validation of Hardware/Software Systems provides a state-of-the-art overview of the current validation and test techniques by covering all aspects of the subject including: modeling of bugs and defects; stimulus generation for validation and test purposes (including timing errors); and design for testability." For researchers working on system-level validation and testing, for tool vendors involved in developing hardware-software co-design tools and for graduate students working in embedded systems and SOC design and implementation, System-level Test and Validation of Hardware/Software Systems will be an invaluable source of reference.